Voluntary Running Attenuates Memory Loss, Decreases Neuropathological Changes and Induces Neurogenesis in a Mouse Model of Alzheimer's Disease. (7th May 2015) - Tapia‐Rojas, Cheril; Aranguiz, Florencia; Varela‐Nallar, Lorena; Inestrosa, Nibaldo C.
Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by loss of memory and cognitive abilities, and the appearance of amyloid plaques composed of the amyloid‐β peptide (Aβ) and neurofibrillary tangles formed of tau protein. It has been suggested that exercise might ameliorate the disease; here, we evaluated the effect of voluntary running on several aspects of AD including amyloid deposition, tau phosphorylation, inflammatory reaction, neurogenesis and spatial memory in the double transgenic APPswe/PS1ΔE9 mouse model of AD. We report that voluntary wheel running for 10 weeks decreased Aβ burden, Thioflavin‐S‐positive plaques and Aβ oligomers in the hippocampus. In addition, runner APPswe/PS1ΔE9 mice showed fewer phosphorylated tau protein and decreased astrogliosis evidenced by lower staining of GFAP. Further, runner APPswe/PS1ΔE9 mice showed increased number of neurons in the hippocampus and exhibited increased cell proliferation and generation of cells positive for the immature neuronal protein doublecortin, indicating that running increased neurogenesis. Finally, runner APPswe/PS1ΔE9 mice showed improved spatial memory performance in the Morris water maze. Altogether, our findings indicate that in APPswe/PS1ΔE9 mice, voluntary running reduced all the neuropathological hallmarks of AD studied, reduced neuronal loss, increased hippocampal neurogenesis and reduced spatial memory loss. These findings support that voluntary exercise might have therapeutic value on AD.